Conservative Treatment for Late-Diagnosed Spinal Accessory Nerve Injury - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2008)
Objective: Spinal accessory nerve (SAN) injuries cause considerable shoulder joint dysfunction and pain, but are often underdiagnosed or diagnosed late. The aim of this study was to present the clinical and electrophysiological features and response to conservative treatment of the patients with late-diagnosed SAN injury. Design: Nine patients diagnosed with SAN injury based on clinical and electrophysiological examinations were evaluated. All patients were treated with a standard physical therapy and rehabilitation program and then received home exercise program. Shoulder pain during rest and activity and pain causing sleep disturbances were evaluated using a visual analog scale. Constant scale investigated shoulder function. Shoulder disability questionnaire evaluated daily living activities. Results were assessed before treatment, after one month of treatment, and years after treatment. Results: According to the electrophysiological studies, seven patients had partial and two patients had total axonal SAN injuries. The delay from the time of injury to diagnosis ranged between 12 and 84 mo (median 14 mo). When compared with the baseline values, visual analog scale, Constant scale, and shoulder disability questionnaire scores were significantly improved in all of the patients. Conclusions: For patients with late-diagnosed SAN injury, conservative treatment seems to be an effective treatment option.
Keywords: Spinal Accessory Nerve Injury; Visual Analog Scale; Constant Scale; Shoulder Disability Questionnaire; Rehabilitation; POSTERIOR TRIANGLE; IATROGENIC INJURY; PALSY; NECK; SHOULDER; DYSFUNCTION; MANAGEMENT; ANATOMY; REPAIR